Digital Transformation in the MSME Accounting Information System and its Contribution to Economic Growth in Indonesia: Systematic Literature Review (SLR) - Hazri Wahyuni Ht. Suhut; Hardea Putriani Fadhila; Iskandar Muda (PT. AHLAL PUBLISHER NUSANTARA, 2025)
This study analyzes the influence of digital transformation on the performance and economic growth of MSMEs in Indonesia through the method Systematic Literature Review (SLR) of 21 journals published in 2018–2025. The study results show that digitalization, including the implementation of Accounting Information Systems (AIS), plays a significant role in improving operational efficiency, financial reporting accuracy, market expansion, and revenue growth for MSMEs. However, the level of technology adoption remains low due to limited digital and accounting literacy, lack of capital and infrastructure, and digital security risks. To optimize its implementation, MSMEs need support through structured training, the use of simple and affordable accounting applications, and multi-stakeholder collaboration. Overall, MSME digitalization has been proven to contribute significantly to strengthening the competitiveness and sustainability of the Indonesian economy. Keyword: Digital Transformation, Accounting Information Systems, MSMEs, and Economic Growth